Development of Economic Independence of Persons with Disabilities through Literacy, Education and Marketing Digitalization Practices in Support of Sustainable Development Goals (SDGs) - Mardiatmi, Bernadin Dwi; Triwahyono, Bambang; Br Pinem, Dahlia; Assumpta Wikantari, Maria; Khoerunisa, Mutia; Sembiring, Bobby Rafael; Samosir, Alfonso (Indonesian Journal of Society Development, 2024)
This community service activity aims to provide solutions that can improve skills for people with disabilities in Yayasan Pendidikan Budi Daya Kasih students as target partners and as proof that academics are present to support Sustainable Development Goals, especially the economic and social empowerment of people with disabilities. The methods used are literacy, pre-test, post-test, and practice of making shops on e-commerce platforms. In general, the results of the marketing digitalization literacy training for students with disabilities at the Budi Daya Kasih Education Foundation have increased the knowledge, skills, and motivation of the Budi Daya Kasih Education Foundation. This is reflected in the increase in pre-test scores with an average of 5.51 increasing to 7.26 in the post-test. In addition, participants successfully created a store account on the Tokopedia platform